Clinical outcomes and diagnostic performance of MRI-Guided Vacuum-Assisted Breast Biopsy – a Systematic Review - Paluchowska, Joanna; Kodura, Alicja; Piwowarczyk, Alicja; Merc, Artur; Łozowski, Jan; Białas, Julia; Szymański, Łukasz; Mordarska, Milena; Gołąbek, Natalia; Piątek, Przemysław (Quality in Sport, 2026)
Background. Breast cancer diagnosis relies heavily on accurate identifying suspicious lesions. Magnetic resonance imaging (MRI) has become one of the most sensitive methods for detecting breast cancer, mainly for invasive carcinomas and ductal carcinoma in situ (DCIS). When lesions which are visible only on MRI, are identified, MRI-guided vacuum-assisted breast biopsy (VABB) is the standard of care. Aim. To systematically review the clinical outcomes, diagnostic accuracy and safety profile of magnetic resonance imaging– MRI-guided vacuum-assisted breast biopsy (VABB) for lesions visible only on MRI. Material and methods. A comprehensive literature search was conducted across major databases, including PubMed and Scopus, up to February 2025 in accordance with PRISMA 2020 guidelines to identify studies on MRI-guided vacuum-assisted breast biopsy (VABB). Two independent reviewers selected original clinical investigations reporting primary outcomes such as technical success, malignancy rates, and underestimation of high-risk lesions, while excluding single case reports and unstratified data. Results. Technical success rates for MRI-guided VABB consistently exceeded 95%. The overall malignancy rate for biopsied lesions ranged from 25% to 30%. High-risk (B3) lesions represented a significant diagnostic challenge, with histological underestimation rates varying widely from 14.6% to 50% across studies. Complication rates were low, mainly consisting of minor hematomas. Conclusions. MRI-guided VABB is a safe and highly accurate technique, essential for managing MRI-only breast lesions. While it effectively rules out malignancy in benign concordant cases, the management of high-risk lesions requires multidisciplinary correlation due to significant upgrade rates.